Influencia del carburo de calcio como pretratamiento en la lixiviación de minerales refractarios auríferos - Esquivel Contreras, Mijael Jonathan (2019)
In this experimental investigation, three types of gold minerals were studied: sulphide mineral with high arsenic content (19.80 g/TM Au and 17.20% As), sulfur mineral with low arsenic content (12.70 g/TM of Au and 0.40% As), carbonaceous gold ore (8.35 g/TM of Au and 0.20% As), the minerals show low recovery of gold by conventional cyanidation, due to the high content of contaminants ( As), encapsulation (FeS2), and preg robbing effect (organic C), for which it was proposed to grind 60% mesh # 200, and then make mesh # 400 mesh using oxidizer calcium carbide in a dose of 2 , 4 and 6 Kg/TM. From the results obtained it is determined that a with a dose of 4 Kg/TM of calcium carbide and in the sulfide mineral with a low content of As (0.20%), the highest recovery is obtained, being 91. 64% gold recovery. It is concluded that the type of mineral and the dosage of calcium carbide as oxidant pretreatment in the trawl influence the recovery of gold by cyanidation by agitation in the bottle. It is concluded that at 95% of significance the type of mineral and the dosage of calcium carbide in the regrind and the interaction of both variables significantly influence the recovery.